Phytochemical profile and antioxidant properties of tomato by-products as affected by extraction solvents and potential application in refined olive oils. (August 2020) - Azabou, Samia; Sebii, Haïfa; Taheur, Fadia Ben; Abid, Yousra; Jridi, Mourad; Nasri, Moncef
Abstract: A comparative evaluation of the effects of the extraction solvent on the phytochemical profile and antioxidant potential of tomato ( Solanum lycopersicum ) by-products (TBP) was done. Results showed significant differences in total and individual phenolic contents and lycopene amount by varying the extraction solvent, which consequently influenced the antioxidant activity of TBP extracts. Significant associations were observed between the antioxidant potency and the total phenolic content. However, the antioxidant assay of some solvent extracts with low total phenolic content such as acetone and hexane extracts, showed good antioxidant effects indicating that some other co-extracted active compounds such as lycopene may also contribute to the overall antioxidant properties. Ethanol (99.5%) is the most suitable solvent to obtain TBP extracts with the highest content of phenolic compounds showing strong antioxidant properties. Taking into account that ethanol is a food grade and environmental friendly solvent, the ethanolic extract from TBP was successfully added into refined olive and olive-pomace oils to enhance their oxidative stability.